Answers

2014-06-22T11:34:59+08:00
2x^2-12x=15
2x^2-12x+36=15+36
2x^2-12x+36= 51
(x-6)^2 = 51
(x-6) = +- 51
1 5 1
The Brainliest Answer!
2014-06-22T13:31:43+08:00
I think this is the right answer. I did the checking and I got it right. ^_^ 

Given: 2x^2-12x=15 

2x^2-12x=15
X^2-6x=15/2
X^2-6x+9=15/2+9
(x-3)^2 = 33/2

(x-3)^2 = 33/2 
x-3 =√33/√2
x-3 =(√33/√2)(√2/√2)
x-3 = ±√66/2   

x-3= √66/2 
x = √66/2 + 3 
x = (6+√66)/2   

x-3= - √66/2 
x =  - √66/2 + 3 
x = (6-√66)/2  

checking:

2x^2-12x=15 
2[(6-√66)/2]^2 – 12[(6-√66)/2] = 15
2[(36-6√66-6√66+66)/4] – [6(6-√66)] = 15
2[(102-12√66)/4] – [36-6√66] = 15 
2[6(17-2√66)/4] – [36-6√66] = 15
 2[3(17-2√66)/2] – [36-6√66] = 15 
3(17-2√66) – [36-6√66] = 15
51 – 6√66 -36+6√66 = 15
 15 = 15
1 5 1
Thank you for making it the best! ^_^